Hippocampal neurogenesis facilitates cognitive flexibility in a fear discrimination task - Martínez-Canabal, Alonso; López-Oropeza, Grecia; Sotres-Bayón, Francisco (Frontiers in Behavioral Neuroscience, 2024)
Hippocampal neurogenesis, the continuous creation of new neurons in the adult brain, influences memory, regulates the expression of defensive responses to threat (fear), and cognitive processes like pattern separation and behavioral flexibility. One hypothesis proposes that neurogenesis promotes cognitive flexibility by degrading established memories and promoting relearning. Yet, empirical evidence on its role in fear discrimination tasks is scarce. In this study, male rats were initially trained to differentiate between two similar environments, one associated with a threat. Subsequently, we enhanced neurogenesis through environmental enrichment and memantine treatments. We then reversed the emotional valence of these contexts. In both cases, neurogenesis improved the rats' ability to relearn the aversive context. Interestingly, we observed increased hippocampal activity, and decreased activity in the prelimbic cortex and lateral habenula, while the infralimbic cortex remained unchanged, suggesting neurogenesis-induced plasticity changes in this brain network. Moreover, when we pharmacologically inhibited the increased neurogenesis with Methotrexate, rats struggled to relearn context discrimination, confirming the crucial role of neurogenesis in this cognitive process. Overall, our findings highlight neurogenesis's capacity to facilitate changes in fear discrimination and emphasize the involvement of a prefrontal-hippocampal-habenula mechanism in this process. This study emphasizes the intricate relationship between hippocampal neurogenesis, cognitive flexibility, and the modulation of fear-related memories.